A Methodology for Embedding Building Information Modelling (BIM) in an Undergraduate Civil Engineering Program - Del Savio, Alexandre Almeida (2022)
Undergraduate programs face the permanent challenge of constantly transforming to keep an up-to-date curriculum according to globalization and internationalization processes. In the case of civil engineers, professional training should respond to the needs of the Architecture, Engineering, Construction, and Operation (AECO) industry. In this context, Building Information Modelling (BIM) constitutes a process involving shared digital representations of built assets to facilitate design, construction, and operations processes within the industry to form a reliable base for decision-making. The present research develops a methodology and a proposal to embed BIM in an undergraduate civil engineering competency-based curriculum. Mixed method research was applied with a descriptive approach and a concurrent design. The results show that it is possible to implement a curricular design to embed BIM transversally. The study concludes that this design was embraced by the AECO industry, as the number of students, the number of employed graduates, and institutional national and international agreements have positively increased from 2017, at the launch of the program, to 2022.